2014
DOI: 10.5694/mja13.00217
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' knowledge of the law on withholding and withdrawing life‐sustaining medical treatment

Abstract: Among doctors who practise in the end-of-life field, there are some significant knowledge gaps about the law on withholding and withdrawing life-sustaining treatment from adults who lack decision-making capacity. Significant consequences for both patients and doctors can flow from a failure to comply with the law. Steps should be taken to improve doctors' legal knowledge in this area and to harmonise the law across Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 5 publications
4
51
0
Order By: Relevance
“…This research demonstrates that to improve compliance with law, increasing legal knowledge is necessary,5 but not sufficient. This points to the need for education that addresses what the law is and the law's rationale and arguments for complying with it.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This research demonstrates that to improve compliance with law, increasing legal knowledge is necessary,5 but not sufficient. This points to the need for education that addresses what the law is and the law's rationale and arguments for complying with it.…”
Section: Discussionmentioning
confidence: 92%
“…Not complying with law can result in patients being denied legal rights and place doctors at legal risk 5 6. Law, which is ultimately a reflection of community values, has an important role to play in medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations to treatment and ACP are promoted as being a support to patient autonomy, yet studies have found that patients and families that document their preferences show no improvement in control over their treatment or correspond with future care preferences. 44 Australian studies also show that physicians have a poor understanding of the law in relation to end of life care, 45 which presents a legal risk to their practice. Like SMS, some ACP models or practice may also neglect to introduce evidenced based information to help patients or their families reach decisions.…”
Section: Patient Centred Carementioning
confidence: 99%